2002
DOI: 10.1377/hlthaff.21.5.182
|View full text |Cite
|
Sign up to set email alerts
|

Challenges To The Pharmacist Profession From Escalating Pharmaceutical Demand

Abstract: Unexpected growth in medication use has escalated demand for pharmacists that has outpaced supply. Responses to the pharmacist shortage include larger workloads and greater use of pharmacist extenders and technology. As the profession has moved from a product orientation (dispensing medications) to a patient focus, clinical training requirements have expanded. However, structural and process barriers, particularly in community and retail pharmacies, must be addressed to improve the medication-use process. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 13 publications
0
73
0
3
Order By: Relevance
“…28,29 Pharmacists' commitment to their profession will be tested frequently by the likelihood of increased future demands on time and resources. 30 Results provide encouraging evidence that students with unpaid employment experience exhibited higher levels of professional commitment. This finding suggests that unpaid pharmacy work experience may facilitate students' development of professional commitment.…”
Section: Discussionmentioning
confidence: 81%
“…28,29 Pharmacists' commitment to their profession will be tested frequently by the likelihood of increased future demands on time and resources. 30 Results provide encouraging evidence that students with unpaid employment experience exhibited higher levels of professional commitment. This finding suggests that unpaid pharmacy work experience may facilitate students' development of professional commitment.…”
Section: Discussionmentioning
confidence: 81%
“…[16] However, the pharmacists approach deeply rooted in the traditional practice of pharmacy pertaining mainly to distributive practice model and is somewhat distant from the other models of practice such as pharmaceutical care, drug information and self-care. [17] In answering questions relating to pharmaceutical care, refer the patient to the doctor when necessary scored the highest whereas, keeping records about patients' medical condition(s), medication and progress and communicate patient's progress on their drug therapy to their doctor scored the lowest score. [8] This may reflect that respondents are not fully convinced that pharmaceutical care activities are their responsibility as pharmacist and are still somewhat distant from the concept as a provider of patient care.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that pharmacists provided higher quality information regarding OTC use of medications (Sahebi and Vahidi, 2009). But during rush-hours, pharmacists are too busy to evaluate patients' conditions and to provide them with necessary information about proper medication use (Cooksey et al, 2002). Second, this false assumption that OTC medications are harmless might lead to carelessly unsupervised usage of NSAIDs (Wilcox et al, 2005) and might cause customers refrain from getting advice.…”
Section: Discussionmentioning
confidence: 99%